Commonwealth Small States, Education and Environmental Uncertainty: Learning from the Sharp End. Issue 4 (4th July 2019) - Crossley, Michael; Louisy, Pearlette
ABSTRACT: This paper examines the Commonwealth's inclusive role in engaging with the distinctive challenges of education provision in small states, an agenda that is often neglected elsewhere. We examine the origins of Commonwealth work on education in small states, the nature of its comparative advantage, its role in facilitating small states' engagement with international education dialogue and regional co-operation, and the demand and potential for ongoing Commonwealth support for education. Particular attention is given to experience within the Caribbean region and to the potential for the Commonwealth and the wider international community to learn from small states in the light of their distinctive educational challenges, achievements and priorities – and, most notably, their experience at the 'sharp end' of environmental uncertainty and climate change.